Analisis Faktor Kesulitan Belajar Bahasa Arab Kelas V Madrasah Ibtidaiyah Pesantren Sabilil Muttaqien (PSM) Kepuhrejo Kediri - Afifah Umudini; Irvan Iswandi; Moh. Mas’ud Arifin (Journal on Education, 2023)
Arabic is a language with a large number of devotees in Indonesia. Learning Arabic has been carried out in Indonesia for a long time, but the results have not been maximized. Various kinds of problems often arise and are almost unsolvable. The problem of teaching Arabic really needs to get serious treatment right away. The purpose of this study was to find out how the difficulties of learning Arabic in Madrasah Ibtidaiyah Islamic Boarding School Sabilil Muttaqien (PSM) Kepuhrejo Kediri, the factors of difficulty learning Arabic and solutions to overcome difficulties learning Arabic in MI PSM Kepuhrejo Kediri. This type of research uses a qualitative research approach that is descriptive in nature. Descriptive research is intended to describe, describe and map facts based on a particular perspective or frame of mind. Solutions that can be made by Arabic teachers are in accordance with the results of interviews in terms of references in overcoming difficulties in learning Arabic for Class V MI PSM Kepuhrejo Kediri. Efforts made by Arabic teachers in overcoming all student difficulties are to familiarize and train students intensively because they are just learning Arabic.